Political communication model: the campaign narratives on Ganjar Pranowo’s YouTube account - Baidawi; Hamdan Daulay (Jurnal Studi Komunikasi, 2024)
Technological advancement has also been used by a number of politicians to express themselves on social media as means of boosting their popularity. This phenomenon is very useful for building political communication in virtual spaces. Therefore, this research examines Ganjar Pranowo's political communication model through his campaign narrative displayed via his personal YouTube account. This research is qualitative research using descriptive and analytical methods in studying Ganjar Pranowo's political communication model. Data collection techniques include selecting content related to the campaign narrative of the @GanjarPranowo’s YouTube account as the primary source. Political communication theory and the elements of argumentation skills– ethos, pathos, and logos. The results of this research found that Ganjar Pranowo used YouTube as a digital platform to build political communication through various content about the campaign. Video content through its campaign narrative enablesGanjar Pranowo to effectively use the elements of ethos, pathos and logos.